Urvvaśīśāpaṃ : āṭṭakkatha - Kuññikrṣṇamēnōn, Pi., 1914- (Kuññikrṣṇamēnōn ; Vitaraṇaṃ, Nāṣanal Bukksṯāḷ, 1983)
Libretto for kathakali, classical dance-drama of kerala, depicting an episode from the Mahābhārata.